2015
DOI: 10.3389/fmicb.2015.00591
|View full text |Cite
|
Sign up to set email alerts
|

When nanoparticles meet biofilms—interactions guiding the environmental fate and accumulation of nanoparticles

Abstract: Bacteria are essential components of all natural and many engineered systems. The most active fractions of bacteria are now recognized to occur as biofilms, where cells are attached and surrounded by a secreted matrix of “sticky” extracellular polymeric substances. Recent investigations have established that significant accumulation of nanoparticles (NPs) occurs in aquatic biofilms. These studies point to the emerging roles of biofilms for influencing partitioning and possibly transformations of NPs in both na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
175
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(178 citation statements)
references
References 59 publications
(76 reference statements)
2
175
0
1
Order By: Relevance
“…49 Importantly, CNMA-GNPs were markedly more effective than free CNMA, which supports the notion that nanodispersions increase interactions with biofilms. 50 As demonstrated earlier, 51 we also claimed that the diminutive sizes of CNMA-GNPs might allow them to invade protective layers of EPS and kill bacteria. Furthermore, the acidic pH in biofilm environments could hydrolyze nanodispersions and promote the sustained release of CNMA.…”
mentioning
confidence: 91%
“…49 Importantly, CNMA-GNPs were markedly more effective than free CNMA, which supports the notion that nanodispersions increase interactions with biofilms. 50 As demonstrated earlier, 51 we also claimed that the diminutive sizes of CNMA-GNPs might allow them to invade protective layers of EPS and kill bacteria. Furthermore, the acidic pH in biofilm environments could hydrolyze nanodispersions and promote the sustained release of CNMA.…”
mentioning
confidence: 91%
“…Due to the resistant nature of biofilms, eradication of biofilm-related diseases/infection is challenging [35]. Efforts are being made to use penetrating capacity of nanoparticles in biofilm studies [36][37][38]. Further application of nanotechnology could be a way to combat biofilm infections.…”
Section: Antibiofilm Assaymentioning
confidence: 99%
“…A difference in diffusion rate and transport into biofilms, as well as effective bioavailability for antimicrobial challenge, may exist between Ag-NPs and Ag 2 S-NPs due to the differences in the transport abilities of dissolved NPs and diffusion of silver ions. Research has shown that silver nanoparticles can effectively transport from culture media to biofilms and that silver ions diffuse much faster than the dissolved NP forms [15] [39]. Additionally, the sulfidation process changes the dissolution rate of silver nanoparticles in water and reduces the release of silver ions.…”
Section: Effects Of Nanoparticle Transport From Media To Biofilmsmentioning
confidence: 99%
“…Current understanding of the biocidal effects of Ag-NPs on planktonic bacterial cells is not sufficient to predict their behavior in biofilms. Recent studies have shown that Ag-NPs can accumulate in biofilms and significantly alter their structure, morphology, and biomass [15] [16] [17] [18]. Additional studies are still needed, however, to characterize the interactions between Ag-NPs and biofilm and elucidate the mechanisms governing the impacts of nanoparticles on natural ecosystems.…”
Section: Introductionmentioning
confidence: 99%